Storytelling festival participation and tourists’ revisit intention - Ko, Sung-Hoon; Kim, Ji-Young; Choi, Yongjun; Kim, Jongsung; Kang, Hyun Chul (Frontiers in Psychology, 2022)
Storytelling is getting increasing attention as one of the effective strategies for revitalizing the local festivals and even regional economies. Yet, the mechanisms through how storytelling helps the success of local festivals are still relatively less known. Using the data from 322 individuals who participated in local festivals using storytelling, our results showed that local festival storytelling is positively related to tourists’ revisit intention. Furthermore, the positive relationship between local festival storytelling and tourists’ revisit intention was serially mediated by authenticity and positive emotion. Theoretical and practical implications are discussed.